Photocatalytic H-2 evolution from water-methanol system by anisotropic InFeO3(ZnO)(m) oxides without cocatalyst in visible light - Narendranath, Soumya B.; Yadav, Ashok Kumar; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2014)
InFeO3(ZnO)(m), series of oxides are found to give unprecedented H-2 evolution from water-methanol mixtures without using any cocatalysts. This family of compounds has an anisotropically layered structure in which Zn/FeOn polyhedra are sandwiched between InO6 octahedral layers. Local structure characterization by X-ray absorption spectroscopy reveals that Zn coordination changes from pentacoordinated to tetrahedral geometry across the series, whereas Fe geometry remains trigonal bipyramidal in all the compounds. This peculiar structure is conducive for a spatial separation of photogenerated charges reducing recombination losses. Band gap energies calculated from absorption spectra indicate potential visible light activity, and this may be due to the orbital mixing of Fe 3d and O 2p as revealed by pre-edge features of X-ray absorption spectra. Band positions are also advantageously placed for a visible light H-2 generation and is indeed found to be the case in methanol-assisted water splitting with standardized hydrogen evolution of similar to 19.5 mmol g(-1) h(-1) for all the catalysts.
Keywords: anisotropic structure; H-2 evolution; InFeO3(ZnO)(m); layered oxide; photocatalytic water splitting